Knowledge preservation management in university libraries / Irsyad Hanif Hutagalung ... [et al.] - Hutagalung, Irsyad Hanif; A. Salim, Tamara; Abdullah Sani, Mad Khir Johari; Mohd Nordin, Nordiana (Faculty of Information Management, 2022)
Libraries are institutions that collect printed and recorded knowledge, manage it in a special way to meet the intellectual needs of its users through various ways of knowledge interaction. In order to maintain the existence of the organization, knowledge management can be done with knowledge management. Knowledge management is the process by which libraries collect knowledge assets and use them to gain a competitive advantage. The challenge that is often faced in the management of knowledge preservation is to provide education to institutions about the meaning and purpose of knowledge preservation. The method used in the preparation of this paper is Systematic Literature Review (SLR). Based on the results of the systematic literature review method (SLR), the research selection was divided into 3 stages of selection. After screening, it was determined that there were 5 (five) articles that were used as references. The knowledge that has been obtained requires special treatment. This special treatment is so that the knowledge that has been possessed is not lost in the future and can be used by the next generation in the form of written in documents or taught orally from generation to generation